2010
DOI: 10.5551/jat.1925
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Pravastatin Therapy in Diabetic Patients Undergoing Complete Coronary Revascularization

Abstract: Aim:The long-term effect of statin therapy in diabetic patients after coronary revascularization is not well established. Accordingly, we sought to determine if whether statin therapy initiated at the time of complete revascularization including percutaneous coronary intervention (PCI) and/or bypass surgery reduces total and cardiac mortality among diabetic patients. Methods: We collected data from 1,138 consecutive patients who underwent complete revascularization (PCI and/or bypass surgery). We then compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…78 Nearly identical findings were reported in 2 observational studies that followed, with significant associations demonstrated between postoperative statin therapy and lower all-cause mortality and cardiac events long term after CABG. 90,91 Of interest, the survival benefits associated with statins after CABG appear to be similar in magnitude to that associated with the use of 2 internal mammary artery grafts compared with the use of only 1 graft. 92 In addition to their lipid-lowering effects, statins appear have important non-lipid-related actions that may contribute to their beneficial effect.…”
Section: Antithrombotic Therapymentioning
confidence: 99%
“…78 Nearly identical findings were reported in 2 observational studies that followed, with significant associations demonstrated between postoperative statin therapy and lower all-cause mortality and cardiac events long term after CABG. 90,91 Of interest, the survival benefits associated with statins after CABG appear to be similar in magnitude to that associated with the use of 2 internal mammary artery grafts compared with the use of only 1 graft. 92 In addition to their lipid-lowering effects, statins appear have important non-lipid-related actions that may contribute to their beneficial effect.…”
Section: Antithrombotic Therapymentioning
confidence: 99%
“…Results from several observational studies proved that statin use was associated with improved survival and reduced MACE occurrence after CABG (37,38). In the present analysis, we focused on exploring the influence of statin adherence and found that poor adherence during the first year was correlated with increased risk of MACE, which suggested that CABG patients could benefit from long-term continuous statin use.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Observational studies have shown that statin use is independently associated with a reduction in all-cause mortality and major adverse cardiovascular events (MACE) after CABG. [7][8][9] However, most of these studies were published decades ago, are limited to singlecenter investigations, or have limited information on medication adherence over time. More recently, in a study based, in part, on the same cohort as the present study, our group reported that ongoing treatment with statins was associated with better long-term survival.…”
Section: Perspectivementioning
confidence: 99%
“…CABG patients, the use of statins has consistently been associated with improved survival and a reduction of MACE in observational studies. 7,9,23 Accordingly, in all guidelines, statins are recommended as a secondary preventive medication for all CABG patients without contraindications. 2,6 However, the use of statins after CABG varies considerably in most observational, real-world studies.…”
Section: Adultmentioning
confidence: 99%